Early Improvement Predicts Clinical Outcomes Similarly in 10 Hz rTMS and iTBS Therapy for Depression - Spitz, Nathen A.; Pace, Benjamin D.; Ten Eyck, Patrick; Trapp, Nicholas T. (Frontiers in Psychiatry, 2022)
Background: Prior studies have demonstrated that early treatment response with transcranial magnetic stimulation (TMS) can predict overall response, yet none have directly compared that predictive capacity between intermittent theta-burst stimulation (iTBS) and 10 Hz repetitive transcranial magnetic stimulation (rTMS) for depression. Our study sought to test the hypothesis that early clinical improvement could predict ultimate treatment response in both iTBS and 10 Hz rTMS patient groups and that there would not be significant differences between the modalities. Methods: We retrospectively evaluated response to treatment in 105 participants with depression that received 10 Hz rTMS (n=68) and iTBS (n=37) to the dorsolateral prefrontal cortex (DLPFC). Percent changes from baseline to treatment 10 (t10), and to final treatment (tf), were used to calculate confusion matrices including negative predictive value (NPV). Treatment non-response was defined as <50% reduction in PHQ-9 scores according to literature, and population, data-driven non-response was defined as <40% for 10 Hz and <45% for iTBS. Results: For both modalities, the NPV related to degree of improvement at t10. NPV for 10 Hz was 80%, 63% and 46% at t10 in those who failed to improve >20%, >10% and >0% respectively; while iTBS NPV rates were 65%, 50%, and 35%. There were not significant differences between protocols at any t10 cut-off assessed, whether research defined 50% improvement as response or data driven kernel density estimates (p 0.22 – 0.44). Conclusion: Patients who fail to achieve >20% improvement by t10 with both 10 Hz rTMS and iTBS therapies have 70% chance of non-response to treatment. With no significant differences between predictive capacities, identifying patients at-risk for non-response affords psychiatrists greater opportunity to adapt treatment strategies.